2019
DOI: 10.1038/s41418-019-0392-8
|View full text |Cite
|
Sign up to set email alerts
|

CSNAP, the smallest CSN subunit, modulates proteostasis through cullin-RING ubiquitin ligases

Abstract: The cullin-RING ubiquitin E3 ligase (CRL) family consists of ~250 complexes that catalyze ubiquitylation of proteins to achieve cellular regulation. All CRLs are inhibited by the COP9 signalosome complex (CSN) through both enzymatic (deneddylation) and non-enzymatic (steric) mechanisms. The relative contribution of these two mechanisms is unclear. Here, we decouple the mechanisms using CSNAP, the recently discovered ninth subunit of the CSN. We find that CSNAP reduces the affinity of CSN toward CRL complexes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…As canonical CSN subunits (CSN1-8) have a oneto-one correspondence to the subunits of the 19S proteasome lid subcomplex (3,28), CSN9 is homologous to DSS1, the smallest component of the 19S lid. While CSN9 is not essential for the assembly and catalytic activity of CSN (27), a recent study has suggested that CSN9 reduces the affinity of CSN-CRL interactions, contributing to steric regulation of CRLs (14). The depletion of CSN9 appears to have a global impact on CRL-associated activities, leading to altered reproductive capacity, suppressed DNA damage response, decreased viability, and delayed cell cycle progression (14).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…As canonical CSN subunits (CSN1-8) have a oneto-one correspondence to the subunits of the 19S proteasome lid subcomplex (3,28), CSN9 is homologous to DSS1, the smallest component of the 19S lid. While CSN9 is not essential for the assembly and catalytic activity of CSN (27), a recent study has suggested that CSN9 reduces the affinity of CSN-CRL interactions, contributing to steric regulation of CRLs (14). The depletion of CSN9 appears to have a global impact on CRL-associated activities, leading to altered reproductive capacity, suppressed DNA damage response, decreased viability, and delayed cell cycle progression (14).…”
Section: Significancementioning
confidence: 99%
“…While CSN9 is not essential for the assembly and catalytic activity of CSN (27), a recent study has suggested that CSN9 reduces the affinity of CSN-CRL interactions, contributing to steric regulation of CRLs (14). The depletion of CSN9 appears to have a global impact on CRL-associated activities, leading to altered reproductive capacity, suppressed DNA damage response, decreased viability, and delayed cell cycle progression (14). It has also been suggested that the C terminus of CSN9 is important in its incorporation within the CSN complex, likely through interactions with CSN3, CSN5, and CSN6 (27).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the activity of CSN is also regulated by both phosphorylation and translocation. It was also found that the loss of CSNAP, the ninth subunit of CSN, causes attenuated DNA damage response after treatment with UV irradiation (Fuzesi-Levi et al, 2020;Rozen et al, 2015). Although CSNAP does not regulate the neddylation of CRLs, it has steric effects on CRLs so that the affinity of CSN for CRLs is promoted when CSNAP is abolished.…”
Section: Csn-mediated Crl Deneddylation In Dna Damage Responsementioning
confidence: 99%
“…Thus, phosphorylation/dephosphorylation in response to signaling processes produces a dynamic heterogeneity of CSN complexes. Moreover, it has recently been recognized that a fraction of cellular CSN contains a non-essential, non-canonical component called CSNAP [ 23 , 24 , 25 ]. A further unexplored source of heterogeneity is provided by the fact that several CSN core subunits occur as paralogs/isoforms [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%